Combined Muscle Motor and Somatosensory Evoked Potentials for Intramedullary Spinal Cord Tumour Surgery - Choi, Il (Yonsei University College of Medicine, 2014)
PURPOSE: To evaluate whether intraoperative neurophysiologic monitoring (IONM) with combined muscle motor evoked potentials (mMEPs) and somatosensory evoked potentials is useful for more aggressive and safe resection in intramedullary spinal cord tumour (IMSCT) surgery. MATERIALS AND METHODS: We reviewed data from consecutive patients who underwent surgery for IMSCT between 1998 and April 2012. The patients were divided into two groups based on whether or not IONM was applied. In the monitored group, the procedures were performed under IONM using 75% muscle amplitude decline weaning criteria. The control group was comprised of patients who underwent IMSCT surgery without IONM. The primary outcome was the rate of gross total excision of the tumour on magnetic resonance imaging at one week after surgery. The secondary outcome was the neurologic outcome based on the McCormick Grade scale. RESULTS: The two groups had similar demographics. The total gross removal tended to increase when intraoperative neurophysiologic monitoring was used, but this tendency did not reach statistical significance (76% versus 58%; univariate analysis, p=0.049; multivariate regression model, p=0.119). The serial McCormick scale score was similar between the two groups (based on repeated measure ANOVA). CONCLUSION: Our study evaluated combined IONM of trans-cranial electrical (Tce)-mMEPs and SEPs for IMSCT. During IMSCT surgery, combined Tce-mMEPs and SEPs using 75% muscle amplitude weaning criteria did not result in significant improvement in the rate of gross total excision of the tumour or neurologic outcome.